2012
DOI: 10.5455/gmj-30-2012-99
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of generalized anxiety disorder in older adults

Abstract: ÖzetBu çalışmanın amacı acil serviste kan gazı elektrolit ve glukoz değerlerinin biyokimyasal elektrolit ve glukoz değerleri yerine kullanılabilirliğini araştırmaktır. Uludağ Üniversitesi Acil servisine Temmuz 2011 ile Ekim 2011 tarihleri arasında başvuran ve acil serviste kan gazı bakılan 18 yaş ve üzeri 1007 hastadan; kan gazı elektrolit ve glukoz ile biyokimyasal elektrolit ve glukoz değerlerinin bakıldığı grup çalışmaya alınmıştır. AbstractIt is aimed to investigate the utility of blood gas electrolyte an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Similarly, depression and anxiety accompanied each other in the study and their incidence was found to be very high. In a study, major depression was observed in 83.7% of patients diagnosed with anxiety 3,25 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, depression and anxiety accompanied each other in the study and their incidence was found to be very high. In a study, major depression was observed in 83.7% of patients diagnosed with anxiety 3,25 .…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of anxiety disorder is about 5% in the general population whereas it increases up to 10% with old age 1,2,25 . The rate of 36.4% reached in the study is very high.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, major depression was observed in 83.7% of patients diagnosed with anxiety. 3,28 The prevalence of anxiety disorder is about 5% in the general population whereas it increases up to 10% with old age. 1,2,28 The rate of 36.4% reached in the study is very high.…”
Section: Discussionmentioning
confidence: 99%
“…3,28 The prevalence of anxiety disorder is about 5% in the general population whereas it increases up to 10% with old age. 1,2,28 The rate of 36.4% reached in the study is very high. Moreover, the rate of depression in the general population was found to be between 3.6% and 8.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The large difference in the rates of GAD prevalence can be explained by the difference in terms of rural versus urban setting of the study population (20). It has been shown that anxiety disorders observed in the elderly are particularly associated with female gender, being single or divorced, suffering multiple chronic medical disorders, and having a low education level (21). As a result of the limitation of our retrospective studies, our data was mainly based on the relation with female gender.…”
Section: Discussionmentioning
confidence: 99%